Writing marginality in modern French literature : from Loti to Genet - Hughes, Edward J. (Edward Joseph), 1953- (Cambridge studies in French., 2001)
"Writing Marginality in Modern French Literature explores how cultural centres require the peripheral, the outlawed, and the deviant in order to define and bolster themselves. It analyses the hierarchies of cultural value which inform the work of six modern French writers: the exoticist Pierre Loti; Paul Gauguin, whose Noa Noa enacts European fantasies about Polynesia; Proust, who analyses such exemplary figures of exclusion and inclusion as the homosexual and the xenophobe; Montherlant, who claims to subvert colonialist values in La Rose de sable; Camus, who pleads an alienating detachment from the cultures of both metropolitan France and Algeria; and Jean Genet.